BIODIVERSITY OF SHARKS AND RAYS IN SOUTH EASTERN INDONESIA - Dharmadi Dharmadi; Fahmi Fahmi; William White (Indonesian Fisheries Research Journal, 2009)
Indonesia has a very diverse shark and ray fauna and is the largest chondrichthyan fisheries in the world. Most of the sharis are caught by longlines and gillnets and rays are caught both as target, e.g. in the tangle net and demersal gillnet fisheries, and as bycatch in other fisheries such as in demersal and drift gittnet, trammel net a-nd long line fisheries.